PUBLIC PERCEPTION TOWARDS THE PUNISHMENT OF CRIMINAL BEATINGS PERPETRATORS IN GEDANGAN THROUGH SOCIOLOGY OF LAW PERSPECTIVE - Fitriani, Ajeng; Rosmaya, Ina (jfpublisher, 2023)
Persecution is a behavior that is clearly intended to cause suffering or injury to another individual, the intentional component must include the purpose of causing suffering or injury to another individual. The persecution can be committed in several ways such as slapping and beating. The regulation on beatings has actually been regulated in Article 170 of the Criminal Code, the article also regulates the punishment imposed on the perpetrators of beatings based on the actual damage committed. There were many cases of beatings in the Gedangan area, Sidoarjo, in 2022. One example is a case of beating committed by 5 perpetrators on St Mandala, Semambung Village, Gedangan, Sidoarjo. Therefore, this research aims to discuss the legal sociology perspective of the beating case. This research used normative legal method which focuses on the discussion of legal issues using laws and regulations, combined with legislative approaches related to the case of beating that occurred in Gedangan, Sidoarjo. The application of the law on beatings in the Gedangan, Sidoarjo involves minors and the diversion is involved first if the act of beating is not a recurrence of an offense. If diversion is not possible due to either a recurrence of the offense or a lack of agreement, then prosecution is conducted by the Public Prosecutor based on the Law.